The Network Model of Depression as a Basis for New Therapeutic Strategies for Treating Major Depressive Disorder in Parkinson’s Disease - D’Ostilio, Kevin; Garraux, Gaëtan (Frontiers in Human Neuroscience, 2016)
The high prevalence of major depressive disorder in people with Parkinson's disease, its negative impact on health-related quality of life and the low response rate to conventional pharmacological therapies call to seek innovative treatments. Here, we review the new approaches for treating major depressive disorder in patients with Parkinson's disease within the framework of the network model of depression. According to this model, major depressive disorder reflects maladaptive neuronal plasticity. Non-invasive brain stimulation using high frequency repetitive transcranial magnetic stimulation over the prefrontal cortex has been proposed as a feasible and effective strategy with minimal risk. The neurobiological basis of its therapeutic effect may involve neuroplastic modifications in limbic and cognitive networks. However, the way this networks reorganize might be strongly influenced by the environment. To address this issue, we propose a combined strategy that includes non-invasive brain stimulation together with cognitive and behavioral interventions.